PENGARUH ROTASI AUDITOR DAN REPUTASI KAP TERHADAP KUALITAS AUDIT DENGAN FEE AUDIT SEBAGAI VARIABEL MODERASI - Rifaldi Rafli; Muhammad Nuryatno Amin (AKUNTABILITAS, 2021)
This study aims to examine the effect of auditor rotation and KAP reputation on audit quality with audit fees as a moderating variable. The sample used in this study is property, real estate, and construction companies listed on the Indonesian Stock Exchange (BEI) in 2017-2019. The number of samples used was 138 companies from 147 companies that met the criteria. The data analysis method used was multiple linear regression and moderated regression analysis (MRA), as well as data processing using SPSS software. The results of this study indicate that Auditor Rotation and KAP Reputation have no effect on Audit Quality. Then the Audit Fee does not play a role in moderating Auditor Rotation and KAP Reputation on Audit Quality.